Bothrops leucurus snake venom protein profile, isolation and biological characterization of its major toxin PLA2s-like - Dias, Êuder Reis; Oliveira, Laudicéia Alves de [UNESP]; Lauria, Pedro Santana Sales; Bordon, Karla de Castro Figueiredo; Domênico, Adriana Moraes Rodrigues [UNESP]; Guerreiro, Marcos Lázaro da Silva; Wiezel, Gisele Adriano; Cardoso, Iara Aimê; Rossini, Bruno César [UNESP]; Marino, Celso Luís [UNESP]; Pimenta, Daniel Carvalho; Arantes, Eliane Candiani; et al. (Elsevier, 2022)
Bothrops leucurus is considered as a snake of medical interest in the State of Bahia, Brazil. However, so far, there are no studies that provide a refined mapping of the composition of this venom. The aim of this work was to better understand the protein composition of B. leucurus snake venom and to isolate and biologically characterize the most abundant toxin, a basic PLA2-like. Shotgun proteomics approach identified 137 protein hits in B. leucurus venom subdivided into 19 protein families. The new basic PLA2-like toxin identified was denominated Bleu-PLA2-like, it and other proteoforms represents about 25% of the total proteins in the venom of B. leucurus and induces myotoxicity, inflammation and muscle damage. Immunoreactivity assays demonstrated that B. leucurus venom is moderately recognized by bothropic and crotalic antivenoms, and on the other hand, Bleu-PLA2-like and its proteoforms are poorly recognized. Our findings open doors for future studies in order to assess the systemic effects caused by this snake venom in order to better understand the toxinological implications of this envenomation and, consequently, to assist in the clinical treatment of victims.
Keywords: Bothrops leucurus; Mass spectrometry; Phospholipase A2; Proteome; Snake venom